Notes on dissimulation in the theatre of Nelson Rodrigues: the case of O beijo no asfalto - Adauto Locatelli Taufer (FronteiraZ, 2013)
The paradigms that determine what is true and false are the reason for to investigate aspects that represent the dissimulation in O beijo no asfalto, by Nelson Rodrigues. Starobinski’s investigations, for whom the society is built upon the solid bases of the conventions that determine how to be and how to act in the social complex mesh; Michel Foucault, for whom the limit between falsehood and truth is a dangerous zone, thanks to the multiple facets that cover the lie -, constitute on the theoretical presuppositions that form the base to the analysis inside. Assuming that the mask is a simulacrum, in fact, it acts as if it was a kind of entry and exit portal that we have in order to travel the maze of social relations. The main goal of this article is to point the different social masks used by “rodriguean” characters on the referred work.